Acceptability of financial incentives to improve health outcomes in UK and US samples. Issue 11 (13th June 2011) - Promberger, Marianne; Brown, Rebecca C H; Ashcroft, Richard E; Marteau, Theresa M
Abstract : In an online study conducted separately in the UK and the US, participants rated the acceptability and fairness of four interventions: two types of financial incentives (rewards and penalties) and two types of medical interventions (pills and injections). These were stated to be equally effective in improving outcomes in five contexts: (a) weight loss and (b) smoking cessation programmes, and adherence in treatment programmes for (c) drug addiction, (d) serious mental illness and (e) physiotherapy after surgery. Financial incentives (weekly rewards and penalties) were judged less acceptable and to be less fair than medical interventions (weekly pill or injection) across all five contexts. Context moderated the relative preference between rewards and penalties: participants from both countries favoured rewards over penalties in weight loss and treatment for serious mental illness. Only among US participants was this relative preference moderated by perceived responsibility of the target group. Overall, participants supported funding more strongly for interventions when they judged members of the target group to be less responsible for their condition, and vice versa. These results reveal a striking similarity in negative attitudes towards the use of financial incentives, rewards as well as penalties, in improving outcomes across a range of contexts, in the UK and the USA. The basis for such negative attitudes awaits further study.